STRATEGI HIJAU MEMODERASI PENGUNGKAPAN EMISI KARBON DAN KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN - Rizqillah, Fahmi; Suripto; Rosini, Iin (Jurnal Riset Terapan Akuntansi, 2024)
In an era of economic uncertainty and global climate change, corporate value is increasingly emphasized, with sustainability demands requiring positive contributions to the environment and society. This study aims to explore how green strategies moderate the relationship between carbon emission disclosure, environmental performance, and corporate value, particularly at PT Astra International Tbk. Using a quantitative approach, this research tests the relationships between carbon emission disclosure, environmental performance, and corporate value with green strategy as a moderating variable, utilizing secondary data from the company's annual reports and sustainability reports listed on the Kompas 100 Index during the period 2018-2022. Data analysis techniques employed panel data regression with Eviews 12 software, involving Chow and Hausman tests to determine the most suitable regression model. The study concludes that Carbon Emission Disclosure significantly negatively influences Corporate Value, while Workplace Environment significantly positively affects Corporate Value. Findings also indicate that Green Strategy moderates the relationship between Carbon Emission Disclosure and Corporate Value, and weakens the relationship between Workplace Environment and Corporate Value. The independent variables collectively have a significant relationship with Corporate Value, and the model used in this research is considered valid. Keywords: Carbon Emissions, Disclosure, Environment, Company, Economy